2011
DOI: 10.2139/ssrn.1967283
|View full text |Cite
|
Sign up to set email alerts
|

Expectations, Realities and Coping Strategies of Elderly Women in a Village of Bangladesh

Abstract: This paper focuses on the socioeconomic status of elderly women, based on 20 elderly women in the village North-Doulatpur in Phulgazi Sadar Upazila, Bangladesh. Information had been collected through in-depth interviews, and then, on the basis of interviews, seven case studies have been prepared. The major findings of this research are that poverty has an important role in the life of elderly village women and that women are more vulnerable than men in their old age, partly because of a patriarchal social stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…A research report on "Expectations, Realities, and coping strategies of Elderly women in a village of Bangladesh" by Tamima Sultana (2011) 18 explored the dignity and honor of the elders in modern society. She also demonstrated that the situation of care for the elderly in Bangladesh is complex.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A research report on "Expectations, Realities, and coping strategies of Elderly women in a village of Bangladesh" by Tamima Sultana (2011) 18 explored the dignity and honor of the elders in modern society. She also demonstrated that the situation of care for the elderly in Bangladesh is complex.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some of the modes of surviving everyday life are found negative by this author, e.g., an old person's conflict with the family members, while others are found positive. These would include the avoidance of conflict, the failure to express one's opinions or wishes, the tolerance of the lack of power within the family and posing no requests to others (Sultana, 2011). Furthermore, a small number of studies dealing with this topic have establish that being religions has a special place in facing life difficulties, particularly poverty 16 and illness.…”
Section: Personal Strategies and Strengths Of People In The Third Lif...mentioning
confidence: 99%
“…Demographic transitions, economic repercussion, and recessions are being overlapped over time as a result of population ageing which is threatening for the developed countries as well as for the developing countries. In every country, males and females played diverse role, obtained different rewards, and experienced different realities causing different life expectancy (Sultana, 2011). The mean age of the population is increasing due to long life.…”
Section: Introductionmentioning
confidence: 99%